2011
DOI: 10.1016/j.freeradbiomed.2011.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative acute kidney injury is associated with hemoglobinemia and an enhanced oxidative stress response

Abstract: Acute kidney injury (AKI) frequently afflicts patients undergoing cardiopulmonary bypass (CPB) and independently predicts death. Both hemoglobinemia and myoglobinemia are independent predictors of postoperative AKI. Release of free hemeproteins into the circulation is known to cause oxidative injury to the kidneys. This study tested the hypothesis that postoperative AKI is associated with both enhanced intraoperative hemeprotein release and increased lipid peroxidation assessed by measuring F 2 -isoprostanes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
131
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(134 citation statements)
references
References 49 publications
1
131
1
1
Order By: Relevance
“…The ability of PM to sequester redox active metal ions may be of particular importance in the context of AKI since increased levels of free circulating iron have been shown to increase oxidative stress and promote AKI associated with rhabdomyolysis, sepsis, and cardiac surgery (4,5,7,27). It has also been shown that AKI increases intracellular levels of free catalytic iron, which increases oxidative stress and renal injury after IR-AKI (35).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability of PM to sequester redox active metal ions may be of particular importance in the context of AKI since increased levels of free circulating iron have been shown to increase oxidative stress and promote AKI associated with rhabdomyolysis, sepsis, and cardiac surgery (4,5,7,27). It has also been shown that AKI increases intracellular levels of free catalytic iron, which increases oxidative stress and renal injury after IR-AKI (35).…”
Section: Discussionmentioning
confidence: 99%
“…Mild AKI is a precursor of chronic kidney disease (CKD), and there is an increased risk of end-stage renal disease (ESRD) in patients with severe AKI (8,11,12,15,62,67). Oxidative stress has been implicated as one of the principal drivers of renal injury and pathophysiology in all of the common causes of AKI (4,25,34,44,45,50). It occurs when the intrinsic antioxidant systems are unable to counteract the effects of excessive production of reactive oxygen species (ROS) and reactive carbonyl species (RCS), which can cause cellular damage via chemical modification to proteins, lipids, and nucleic acids (18,49,58).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms underlying postoperative AKI are not well defined but are associated with intraoperative hemolysis, hypotension, altered autoregulation of renal perfusion, inflammation, and oxidative stress [2,3,4]. Cardiopulmonary bypass (CPB) hemolyzes erythrocytes, increasing plasma concentrations of free hemoglobin [3].…”
Section: Introductionmentioning
confidence: 99%
“…Circulating hemeproteins damage the kidney by scavenging nitric oxide and increasing lipid peroxidation [5]. We previously demonstrated that postoperative AKI is associated with enhanced intraoperative hemeprotein release and enhanced lipid peroxidation in patients undergoing CPB [3]. Heme oxygenase-1 (HO-1), the inducible isoform of heme oxygenase, catalyzes the degradation of heme.…”
Section: Introductionmentioning
confidence: 99%